2018
DOI: 10.1038/s41598-018-29018-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia induces therapeutic effectiveness and potentiates adjuvant therapy with non-targeted and targeted drugs in an in vitro model of human malignant melanoma

Abstract: In the present study, we have aimed to characterize the intrinsic, extrinsic and ER-mediated apoptotic induction by hyperthermia in an in vitro model of human malignant melanoma and furthermore, to evaluate its therapeutic effectiveness in an adjuvant therapeutic setting characterized by combinational treatments with non-targeted (Dacarbazine & Temozolomide) and targeted (Dabrafenib & Vemurafenib) drugs. Overall, our data showed that both low (43 °C) and high (45 °C) hyperthermic exposures were capable of indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 71 publications
4
52
0
Order By: Relevance
“…In the present study, we utilized two in vivo murine models of malignant melanoma and colon carcinoma in order to examine hyperthermia's therapeutic effectiveness. Firstly, we aimed to validate our previous in vitro findings showing hyperthermia's capacity to activate apoptotic cell death in human malignant melanoma (A375) cells (39). For this reason, an in vivo murine model of malignant melanoma was utilized by injecting B16-F10 cells into the subcutaneous tissue of the back of the neck of C57BL/6 female mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we utilized two in vivo murine models of malignant melanoma and colon carcinoma in order to examine hyperthermia's therapeutic effectiveness. Firstly, we aimed to validate our previous in vitro findings showing hyperthermia's capacity to activate apoptotic cell death in human malignant melanoma (A375) cells (39). For this reason, an in vivo murine model of malignant melanoma was utilized by injecting B16-F10 cells into the subcutaneous tissue of the back of the neck of C57BL/6 female mice.…”
Section: Resultsmentioning
confidence: 99%
“…According to their findings, the induction of cell death pathways is dependent on i) cancer cell type, ii) temperature and iii) duration of heat exposure (40,41). Previously we demonstrated that hyperthermia induces various apoptotic cascades and enhances the therapeutic effectiveness of non-targeted and targeted drugs in an in vitro model of human malignant melanoma (39). To this end, the aim of this study was to validate our previous in vitro findings in two in vivo models of murine malignant melanoma and colon carcinoma in an attempt to demonstrate hyperthermia's effectiveness as a cancer treatment option.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While temperature rises between the “fever range” and “thermal ablation range” at 41–43°C, tumor cells died predominantly by apoptosis with a balance between pro-apoptosis and anti-apoptosis. This process involves the induction of CHOP, the alterations in calcium levels and the activation of ER proteases, calpain–calpastatin proteolytic system and caspase mediated apoptosis ( 30 , 31 ). This process also accompanies with the upregulation of eIF2 α phosphorylation.…”
Section: Hyperthermia Is a Strong Icd Inducermentioning
confidence: 99%
“…Regarding non-ionized 4T1, they show maximum 20% toxicity in the three concentrations tested, opposed to ionized 4T1 that in the concentrations 400 and 600 μg/ml of Fe3O4 show high toxicity (~58% and 65% respectively), indicating ionizationdependent toxicity. Fe3O4 core Αg shell NPs because of the toxic effect of Ag NPs on their own, compared to Au NPs that are considered to be the less toxic metal NPs for in vivo applications, do not seem to act as heating mediators [7,14]. Fe3O4 core Αg shell NPs show no ionization-dependent toxicity in both cell lines.…”
Section: Discussionmentioning
confidence: 99%